PENATALAYANAN MEDIA SOSIAL DARI PERSPEKTIF JEROME POLIN - Sartika, Meitha; Purba, Osaca Yeremia Agave (The Way: Jurnal Teologi dan Kependidikan, 2024)
This research aims to ensure that the content or information available through social media is beneficial to its users, whether it is constructive or not, and whether it is useful or not. It requires social media content creators to be creative and adaptive, so they can generate something positive, good, and relevant for users. The method used in this research is qualitative, with literature review and observation. The findings reveal that, as disciples of Christ, as those who have been justified, and as servants of Christ, it is proper to act wisely when using social media, so as not to fall into the misuse of social media for things that are disgraceful and evil in God's sight, and to be a blessing to others through social media. It can be concluded that through collaboration, the variety of spiritual content becomes more complete and complementary, catering to both children and adults, discussing issues of body, soul, and spirit in humans, and expanding knowledge of true teachings to inspire many and be a blessing.